Pengaruh Intangible Asset, Political Connection, dan Tunneling Incentives Terhadap Transfer Pricing Aggressiveness (Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Suci Lestari; Mhd Hasymi (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2022)
Transfer pricing as a classic issue in the world of taxation causes loss of potential tax that will be a state revenue. Multinational companies use transfer pricing aggressiveness as a result of the relationship with related parties for tax avoidance practice. The purpose of this study is to examine the effect of intangible assets, political connection, and tunneling incentives to transfer pricing aggressiveness. This study analyzed 13 samples of mining companies companies listed on the Indonesia Stock Exchange (IDX) from the period 2014 to 2018. This research was conducted with a quantitative approach with panel data analyzed using multiple regression analysis. The results of this study find that intangible assets is positively associated with transfer pricing aggressiveness, while political connection and tunneling incentives are not related to transfer pricing aggressiveness.